Context Matters for Tone and Intonation Processing in Mandarin. (March 2022) - Liu, Min; Chen, Yiya; Schiller, Niels O.
In tonal languages such as Mandarin, both lexical tone and sentence intonation are primarily signaled by F0. Their F0 encodings are sometimes in conflict and sometimes in congruency. The present study investigated how tone and intonation, with F0 encodings in conflict or in congruency, are processed and how semantic context may affect their processing. To this end, tone and intonation identification experiments were conducted in both semantically neutral and constraining contexts. Results showed that the overall performance of tone identification was better than that of intonation. Specifically, tone identification was seldom affected by intonation information irrespective of semantic contexts. However, intonation identification, particularly question intonation, was susceptible to the final lexical tone identity and affected by the semantic context. In the semantically neutral context, questions ending with a rising tone and a falling tone were equally difficult to identify. In the semantically constraining context, questions ending with a falling tone were much better identified than those ending with a rising tone. This perceptual asymmetry suggests that top-down information provided by the semantically constraining context can play a facilitating role for listeners to disentangle intonational information from tonal information, but mainly in sentences with the lexical falling tone in the final position.